2021
DOI: 10.2147/jpr.s292335
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intradiscal Platelet-Rich Plasma Injection for Management of Discogenic Lower Back Pain: A Meta-Analysis

Abstract: Objective Although several researches of animal and human subjects have yielded promising results regarding intradiscal injection of platelet-rich plasma (PRP) for the management of intervertebral disc (IVD) pathologies, small sample sizes and unstandardized graft preparation procedures hampered these research efforts. Therefore, we conducted a meta-analysis to evaluate the effectiveness of intradiscal PRP injection for the treatment of discogenic lower back pain. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Emerging data have suggested that intradiscal PRP therapy with < fivefold increases in platelet concentrations may have therapeutic value for certain patients with CLDP [ 8 , 13 , 19 , 20 ]. Our results add to the current literature showing long-term benefits of intradiscal PRP in the management of patients with CLDP [ 9 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging data have suggested that intradiscal PRP therapy with < fivefold increases in platelet concentrations may have therapeutic value for certain patients with CLDP [ 8 , 13 , 19 , 20 ]. Our results add to the current literature showing long-term benefits of intradiscal PRP in the management of patients with CLDP [ 9 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several in vivo and in vitro investigations have shown the utility of PRP for IVD repair and regeneration ( Obata et al, 2012 ; Wang et al, 2013 ; Pirvu et al, 2014 ). In addition as a therapeutic strategy, PRP has the merits of being low-cost, ease of preparation, ease of application, and autologous sources without rejection reaction ( Chang and Park, 2021 ). Nevertheless, in view of the possible negative consequences of ossification, inflammation, and vascularization, more research on standardized formulations is of great necessity to validate the effectiveness and safety of PRP.…”
Section: Current Treatments For Intervertebral Disc Degeneration Diseasesmentioning
confidence: 99%
“…71 Recently, several meta-analyses demonstrated that intradiscal PRP injection had shown beneficial effects in controlling pain and improving disabilities in patients with LBP, but there was a paucity of high-quality studies to give conclusive evidence. 72,73 Therefore, more clinical studies, especially RCTs with multiple outcome parameters, are necessary for evaluating the true efficacy of this treatment. 74 Moreover, according to the American Society of Interventional Pain Physicians guidelines, the qualitative evidence for intradiscal PRP injection in the treatment of LBP has been assessed as level III, based on the available evidence including RCT, observational studies, metaanalysis, and systematic review.…”
Section: Platelet-rich Plasmamentioning
confidence: 99%
“…Recently, several meta‐analyses demonstrated that intradiscal PRP injection had shown beneficial effects in controlling pain and improving disabilities in patients with LBP, but there was a paucity of high‐quality studies to give conclusive evidence 72,73 . Therefore, more clinical studies, especially RCTs with multiple outcome parameters, are necessary for evaluating the true efficacy of this treatment 74 .…”
Section: Platelet‐rich Plasmamentioning
confidence: 99%
See 1 more Smart Citation